14
$\begingroup$

Let $T^d:=\{(x_1,..,x_d):x_i \geq 0, \sum_{i=1}^{d}x_i \leq 1\}$ be the standard simplex in $\mathbb{R}^d$. Compute the integral $$\int_{T^d} x_1^{\nu_1-1}x_2^{\nu_2-1}...x_d^{\nu_d-1}(1-x_1-...-x_d)^{\nu_0-1}$$ where $\nu_i>0$.

Remark: I know the answer is $$\frac{\prod_{i=0}^{d}\Gamma(\nu_i)}{\Gamma(\sum_{i=0}^{d}\nu_i)}.$$ I evaluated for the case $d=2$ by using the transformation $(p-1)\iiint\limits_{T^{3}} x^{m-1}y^{n-1}z^{p-2} \mathrm{d}z\mathrm{d}y\mathrm{d}x= \iint\limits_{T^{2}} x^{m-1}y^{n-1}(1-x-y)^{p-1}\mathrm{d}y\mathrm{d}x$

and the substitutions $ \left\{\begin{matrix}x=u^2& &\\y=v^2& &\\z=w^2& &\end{matrix}\right.$and $ \left\{\begin{matrix}u=r\sin\varphi\cos\theta& &\\v=r\sin\varphi\sin\theta& &\\w=r\cos\varphi& &\end{matrix}\right.,$ but this method is complex for computing the general case.

$\endgroup$
  • 2
    $\begingroup$ Your indices are off by one. In the present form, the last factor is a (possibly negative) power of $0$, and the answer you suggest doesn't depend on $a_0$. Also note that punctuation at the end of a displayed equation needs to go inside the double dollar signs (preferably set off from the equation by a \; space) since otherwise it ends up on the next line. $\endgroup$ – joriki Oct 4 '12 at 12:00
  • $\begingroup$ i think these are dirichlet integrals, maybe mathworld.wolfram.com/DirichletIntegrals.html $\endgroup$ – mike Oct 4 '12 at 14:24
  • $\begingroup$ What are the elements in the sum when you define $T^d$? $\endgroup$ – Davide Giraudo Oct 4 '12 at 20:11
  • $\begingroup$ Edited. It's the standard simplex. The integral is a generalised Beta function (multinomial type), I have not found any literature about how to compute it $\endgroup$ – user31899 Oct 4 '12 at 20:26
  • $\begingroup$ Indeed, the integral is the normalising constant in the pdf of the Dirichlet distribution. $\endgroup$ – StubbornAtom Jan 24 '18 at 14:47
8
$\begingroup$

For any $a \in \mathbb{R}-\{0\}$ and $m,n \in (0,+\infty)$ one has \begin{align*} \frac{1}{a^{m+n-1}}\int_{0}^{a}y^{m-1}(a-y)^{n-1}\mathrm{d}y&=\frac{1}{a^{m+n-1}}\int_{0}^{a}a^{m+n-2}\left(\frac{y}{a}\right)^{m-1}\left(1-\frac{y}{a}\right)^{n-1}\mathrm{d}y\\&=\frac{1}{a}\int_{0}^{a}\left(\frac{y}{a}\right)^{m-1}\left(1-\frac{y}{a}\right)^{n-1}\mathrm{d}y\\&=\int_{0}^{1}x^{m-1}(1-x)^{n-1}\mathrm{d}x \end{align*} Thus $\int_{0}^{a}y^{m-1}(a-y)^{n-1}\mathrm{d}y=a^{m+n-1}B(m,n)$. With above observation we can integrate $x_1^{\nu_1-1}...x_d^{\nu_d-1}(1-x_1-...-x_d)^{\nu_{0}-1}$ over $T^{d}$ by integrating out variables one at each step \begin{align*} &\mathrel{\phantom{=}} \int_{T^{d}}x_1^{\nu_1-1}...x_d^{\nu_d-1}(1-x_1-...-x_d)^{\nu_{0}-1}\mathrm{d}\boldsymbol x\\ &=\int_{0}^{1}\int_{0}^{1-x_1}...\int_{0}^{1-x_1-...-x_{d-1}}x_1^{\nu_{1}-1}x_2^{\nu_{2}-1}...x_d^{\nu_{d}-1}(1-x_1-...x_d)^{\nu_{0}-1}\mathrm{d}x_d...\mathrm{d}x_2\mathrm{d}x_1\\ &=\int_{0}^{1}x_1^{\nu_{1}-1}\int_{0}^{1-x_1}x_2^{\nu_{2}-1}...\int_{0}^{1-x_1-...-x_{d-1}}x_d^{\nu_{d}-1}(1-x_1-...x_d)^{\nu_{0}-1}\mathrm{d}x_d...\mathrm{d}x_2\mathrm{d}x_1\\&=B(\nu_0,\nu_d)\int_{0}^{1}x_1^{\nu_{1}-1}\int_{0}^{1-x_1}x_2^{\nu_{2}-1}...\int_{0}^{1-x_1-...-x_{d-2}}x_{d-1}^{\nu_{d-1}-1}(1-x_1-...x_{d-1})^{\nu_{0}+\nu_{d}-1}\mathrm{d}x_{d-1}...\mathrm{d}x_2\mathrm{d}x_1\\&=B(\nu_{d-1},\nu_{0}+\nu_{d})B(\nu_0,\nu_d)\int_{0}^{1}x_1^{\nu_{1}-1}...\int_{0}^{1-x_1...-x_{d-2}}x_{d-2}^{\nu_{d-2}-1}(1-x_1-...-x_{d-2})^{\nu_{0}+\nu_{d-1}+\nu_{d}-1}\mathrm{d}x_{d-2}...\mathrm{d}x_1\\&=...\\&=B(\nu_1,\nu_0+\nu_d+\nu_{d-1}+...+\nu_{2})B(\nu_2,\nu_0+\nu_d+\nu_{d-1}+...+\nu_{3})...B(\nu_{d-1},\nu_0+\nu_d)B(\nu_{0},\nu_d)\\&=\frac{\Gamma(\nu_{0})\Gamma(\nu_{1})...\Gamma(\nu_{d})}{\Gamma(\nu_{0}+\nu_{1}+...+\nu_{d})}\\&=\frac{\Gamma(\boldsymbol {\nu})}{\Gamma(|\boldsymbol {\nu}|)} \end{align*}

$\endgroup$
4
$\begingroup$

Put $(n_0,n_1,\ldots, n_d)=:n$, $\sum_{k=0}^d n_k=:|n|$ and for $\lambda\geq0$ define $$Q(n,\lambda):=\int\nolimits_{\lambda T^d}\prod_{1\leq k\leq d} x_k^{n_k-1} \ (\lambda -x_1-\ldots -x_d)^{n_0-1}\ {\rm d}(x)\ .$$ The substitution $x:=\lambda y\ (y\in T^d)$ gives $$Q(n,\lambda)=\lambda^{d+|n|-(d+1)}\int\nolimits_{T^d}\prod_{1\leq k\leq d} y_k^{n_k-1} \ (1 -y_1-\ldots -y_d)^{n_0-1}\ {\rm d}(y)=\lambda^{|n|-1} Q(n,1)\ .$$ Letting the "outer integration" be with respect to the last variable we now obtain $$\eqalign{Q(n,1)&=\int_0^1 x^{n_d-1}\int\nolimits_{(1-x)T^{d-1}}\prod_{1\leq k\leq d-1} x_k^{n_k-1} (1-x_1-\ldots-x_{d-1}-x)^{n_0-1}\ {\rm d}(x')\ dx\cr &= \int_0^1 x^{n_d-1} Q(n',1-x)\ dx=Q(n',1)\int_0^1 x^{n_d-1}(1-x)^{|n'|-1}\ dx\ . \cr}$$ Here the last integral evaluates to $B(|n'|,n_d)$, so that we end up with the recursion $$Q(n,1)=Q(n',1) B(|n'|,n_d)\ .$$ From here it should not be too difficult to arrive at the desired result.

$\endgroup$
4
$\begingroup$

If one wishes to use a change of variables, an appropriate transformation would be

$(x_1,x_2,...,x_d)\to(y_1,y_2,...,y_d)$ such that

$\qquad y_1=x_1+x_2+\cdots+x_{d-1}+x_d$

$\qquad y_1y_2=x_1+x_2+\cdots+x_{d-2}+x_{d-1}$

$\qquad y_1y_2y_3=x_1+x_2+\cdots+x_{d-3}+x_{d-2}$

$\qquad \vdots$

$\qquad \prod_{i=1}^{d-1} y_i=x_1+x_2$

$\qquad \prod_{i=1}^{d} y_i=x_1$

$\implies x_1=y_1y_2y_3\,...\,y_{d-1}y_d$

$\qquad x_2=y_1y_2y_3\,...\,y_{d-1}(1-y_d)$

$\qquad x_3=y_1y_2y_3\,...\,y_{d-2}(1-y_{d-1})$

$\qquad \vdots$

$\qquad x_{d-1}=y_1y_2(1-y_3)$

$\qquad x_d=y_1(1-y_2)$ $\qquad\qquad$, so that $0\le y_i\le 1$ for all $i=1,2,...,d$.

The Jacobian of the transformation can be calculated as $\det(J)=-\prod_{i=1}^{d-1} y_i^{d-i}$

The integral thus reduces to

$$\displaystyle I=\int_0^1 y_1^{({\sum_{i=1}^{d}\nu_i-1})}(1-y_1)^{\nu_0-1}\mathrm{d}y_1\int_0^1 y_2^{({\sum_{i=1}^{d-1}\nu_i-1})}(1-y_2)^{\nu_d-1}\mathrm{d}y_2\cdots\int_0^1 y_{d-1}^{(\nu_1+\nu_2-1)}(1-y_{d-1})^{\nu_3-1}\mathrm{d}y_{d-1}\int_0^1 y_{d}^{(\nu_1-1)}(1-y_{d})^{\nu_2-1}\mathrm{d}y_{d}$$

$$=B\left(\sum_{i=1}^d\nu_i,\nu_0\right)B\left(\sum_{i=1}^{d-1}\nu_i,\nu_d\right)\cdots B\left(\nu_1+\nu_2,\nu_3\right)B\left(\nu_1,\nu_2\right)$$

$\qquad\qquad\qquad\quad=\displaystyle\frac{\prod_{i=0}^d\Gamma(\nu_i)}{\Gamma\left(\sum_{i=0}^d\nu_i\right)}$

$\endgroup$
  • $\begingroup$ That's a very cool change of variables. Is this from a textbook/paper? $\endgroup$ – becko Sep 24 '18 at 15:57
  • $\begingroup$ @becko Not that I know of. $\endgroup$ – StubbornAtom Sep 24 '18 at 16:08
  • 1
    $\begingroup$ Setting $y_i = \sin^2(\theta_i)$ makes this much easier to visualize. $\endgroup$ – becko Sep 24 '18 at 16:23
  • 1
    $\begingroup$ This is a mapping from the unit hyper-sphere to the simplex (en.wikipedia.org/wiki/N-sphere#Spherical_coordinates) $\endgroup$ – becko Sep 24 '18 at 16:39
  • $\begingroup$ I meant $n$-sphere. $\endgroup$ – becko Sep 24 '18 at 16:47
3
$\begingroup$

Another, elegant way to perform your integration is explained by Jaynes in §18.10 of "Probability Theory: The Logic of Science". It uses a Laplace transform:

Slightly modifying your notation, your integral can be rewritten as

$$I(r) := \int_{[0,\infty)^n} x_1^{a_1} \dotsm x_n^{a_n} \,\mathrm{\delta}(r-x_1-\dotsb-x_n)\, \mathrm{d}x_1\dotsm\mathrm{d}x_n\qquad\text{with $r=1$}.$$

Note that the delta allows us to extend the integration to $\infty$, and renders the integration bounds independent from one another.

Now take the Laplace transform of $I(r)$ and eliminate the delta from it:

$$\int_0^{\infty} \exp(-zr) I(r)\,\mathrm{d}r = \int_{[0,\infty)^n} x_1^{a_1} \dotsm x_n^{a_n} \,\exp[-z(x_1+\dotsb+x_n)]\, \mathrm{d}x_1\dotsm\mathrm{d}x_n \\= \prod_{i=1}^n\int_0^\infty x_i^{a_i}\,\exp(-z x_i)\,\mathrm{d}x_i =\prod_{i=1}^n\frac{a_i!}{z^{a_i+1}}.$$

Now take the inverse Laplace transform of the last expression to obtain back $I(r)$:

$$I(r) = \frac{1}{2\pi\mathrm{i}}\int_{-\mathrm{i}\infty}^{+\mathrm{i}\infty} \exp(rz)\,\prod_{i=1}^n\frac{a_i!}{z^{a_i+1}}\,\mathrm{d}z \\=\frac{\prod_{i=1}^n a_i!}{(n+\sum_ia_i-1)!} r^{n+\sum_ia_i-1}$$

and evaluate it at $r=1$. The path of integration of the last integral "passes to the right of the origin, and is closed by an infinite semicircle over the left half-plane" (Jaynes).

Hope this helps.

$\endgroup$
1
$\begingroup$

Here is the solution form my professor at TU Darmstadt: We start by realizing \begin{align*} \int_{[0,\infty]^{n}}\prod_{i=1}^{n}\exp(-x_{i})x_{i}^{\alpha_{i}-1}\mathrm{d}\mathbf{x} & =\prod_{i=1}^{n}\int_{0}^{\infty}\exp(-x_{i})x_{i}^{\alpha_{i}-1}\mathrm{d}x_{i}=\prod_{i=1}^{n}\Gamma(\alpha_{i}). \end{align*} We simplify \begin{align*} & \exp\underbrace{\left(-\sum_{i=1}^{n}x_{i}\right)}_{=-t}\prod_{i=1}^{n}x_{i}^{\alpha_{i}-1}\\ & =\exp\left(-t\right)\prod_{i=1}^{n-1}\left(tp_{i}\right)^{\alpha_{i}-1}\left(t\left(1-\sum_{j=1}^{n-1}p_{j}\right)\right)^{\alpha_{n}-1}\\ & =\left(\exp\left(-t\right)t^{\left(\sum_{i=1}^{n}\alpha_{i}\right)-n}\right)\left(\prod_{i=1}^{n-1}p_{i}^{\alpha_{i}-1}\left(1-\sum_{j=1}^{n-1}p_{j}\right)^{\alpha_{n}-1}\right) \end{align*} using the transformations \begin{align*} t & =\sum_{j=1}^{n}x_{j},\\ x_{i} & =tp_{i},\\ x_{n} & =t\left(1-\sum_{i=1}^{n-1}p_{i}\right), \end{align*} which yields a Jacobian \begin{align*} \mathbf{J} & =\begin{bmatrix}t\mathbf{I} & \mathbf{p}\\ -t\mathbf{1}_{n-1}^{\intercal} & \left(1-\mathbf{1}_{n-1}^{\intercal}\mathbf{p}\right) \end{bmatrix}. \end{align*} The blockdiagonal structure of the upper $(n-1)\times(n-1)$ matrix makes the determinant

\begin{align*} \det\mathbf{J}=\left(\left(1-\mathbf{1}_{n-1}^{\intercal}\mathbf{p}\right)-\left(-t\mathbf{1}_{n-1}^{\intercal}\right)\left(t\mathbf{I}\right)^{-1}\mathbf{p}\right)\det\left(t\mathbf{I}\right)=t^{n-1}. \end{align*}

Now, we use the substitution formula \begin{align*} & \int_{[0,\infty]^{n}}\prod_{i=1}^{n}\exp(-x_{i})x_{i}^{\alpha_{i}-1}\mathrm{d}\mathbf{x}\\ & =\int_{0}^{\infty}\left(\exp\left(-t\right)t^{\left(\sum_{i=1}^{n}\alpha_{i}\right)-n}\right)\int_{[0,1]^{n-1}}\prod_{i=1}^{n-1}p_{i}^{\alpha_{i}-1}\left(1-\sum_{j=1}^{n-1}p_{j}\right)^{\alpha_{n}-1}t^{n-1}\mathrm{d}\mathbf{p}~\mathrm{d}t\\ & =\int_{0}^{\infty}\left(\exp\left(-t\right)t^{\left(\sum_{i=1}^{n}\alpha_{i}\right)-1}\right)\mathrm{d}t\int_{[0,1]^{n-1}}\prod_{i=1}^{n-1}p_{i}^{\alpha_{i}-1}\left(1-\sum_{j=1}^{n-1}p_{j}\right)^{\alpha_{n}-1}\mathrm{d}\mathbf{p}\\ & =\Gamma\left(\sum_{i=1}^{n}\alpha_{i}\right)\int_{[0,1]^{n-1}}\prod_{i=1}^{n-1}p_{i}^{\alpha_{i}-1}\left(1-\sum_{j=1}^{n-1}p_{j}\right)^{\alpha_{n}-1}\mathrm{d}\mathbf{p} \end{align*} and, thus, we have

\begin{align*} \int_{[0,1]^{n-1}}\prod_{i=1}^{n-1}p_{i}^{\alpha_{i}-1}\left(1-\sum_{j=1}^{n-1}p_{j}\right)^{\alpha_{n}-1}\mathrm{d}\mathbf{p}=\frac{\prod_{i=1}^{n}\Gamma(\alpha_{i})}{\Gamma\left(\sum_{i=1}^{n}\alpha_{i}\right)}. \end{align*}

$\endgroup$
1
$\begingroup$

Another way is the following: we can rewrite the integral as $$ I_n(a)=\int_{\mathbb R_+^n} x_1^{\nu_1-1}\cdots x_n^{\nu_n-1} \delta(x_1+\cdots+x_n-a) dx_1 \cdots dx_n $$ with $n=d+1$ and $\nu_0\equiv \nu_n$. By rescaling each $x_i$ by $a$, we see that $$ I_n(a)=a^{\nu_1+\cdots + \nu_n-1} I_n(1). $$ Then, $$\begin{aligned} I_n(1) &=\int_0^1 dx\, x^{\nu_n-1} I_{n-1}(1-x) \\ &= I_{n-1}(1)\int_0^1 x^{\nu_n-1} (1-x)^{\nu_1+\cdots+\nu_{n-1}-1}dx\\ &=I_{n-1}(1) B(\nu_n,\nu_1+\cdots+\nu_{n-1}). \end{aligned}$$ Proceeding by induction, $$ I_n(1)=I_1(1) B(\nu_2, \nu_1) B(\nu_3,\nu_1+\nu_2)\cdots B(\nu_{n-1},\nu_1+\cdots + \nu_{n-2}) B(\nu_n, \nu_1+\cdots+\nu_{n-1}) $$ and after a few cancellations between numerator and denominator, $$ I_n(1)=\frac{\Gamma(\nu_1)\cdots \Gamma(\nu_n)}{\Gamma(\nu_1+\cdots+\nu_n)}\,. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.